2016
DOI: 10.1007/s10897-016-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling Assistants: an Integral Piece of the Evolving Genetic Counseling Service Delivery Model

Abstract: This study explores the potential impact of the genetic counseling assistant (GCA) position on the efficiency of the genetic counseling field, evaluates attitudes regarding expansion of the genetic counseling field to include the GCA, and presents data on GCA endeavors and GCA job tasks as reported by GCAs, certified genetic counselors (CGCs), and program directors (PDs). Data on GCA roles and attitudes toward different aspects of the GCA position were collected via surveys of CGCs who have worked with GCAs, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 16 publications
7
58
0
Order By: Relevance
“…Applying this frame to variant review activities, we can identify tasks that could be performed by other members of the healthcare team to allow genetic counselors to focus on tasks higher in their scope of practice. For example, some aspects of gathering additional data could be performed by others, such as genetic counseling assistants (Pirzadeh-Miller et al 2017), while critical review of the available data and discussion of the classification with cardiologist and geneticist colleagues is likely best performed by genetic counselors.…”
Section: Discussionmentioning
confidence: 99%
“…Applying this frame to variant review activities, we can identify tasks that could be performed by other members of the healthcare team to allow genetic counselors to focus on tasks higher in their scope of practice. For example, some aspects of gathering additional data could be performed by others, such as genetic counseling assistants (Pirzadeh-Miller et al 2017), while critical review of the available data and discussion of the classification with cardiologist and geneticist colleagues is likely best performed by genetic counselors.…”
Section: Discussionmentioning
confidence: 99%
“…Delegation to numerous staff positions including personnel to manage insurance authorization (Uhlmann, Schwalm, & Raymond, ), genetic counseling assistants (Pirzadeh‐Miller et al, ), and additional clinical personnel (i.e. non‐genetics professionals) can directly aid in the genetic counseling process (Cohen et al, ; Cohen & McIlvried, ; O'Shea et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This increasing demand for GCs across multiple sectors of healthcare, including clinical, commercial, and other domains, has led to concerns about a shortage of genetic counselors (Hoskovec et al, ; Pan, Yashar, Pothast, & Wicklund, ) such that the supply of GCs in direct patient care will likely not meet projected demand until 2030 (Hoskovec et al, ). The genetic counseling profession has adopted multifaceted strategies to address this shortage including (a) expansion of the number and size of Accreditation Council for Genetic Counseling (ACGC) accredited Genetic Counseling Programs, (b) the adoption of alternative service delivery models such as telephone genetic counseling, telemedicine, and group counseling (Cohen et al, ; Kinney et al, ; Platten et al, ), (c) the development of genetic counseling assistant positions (Pirzadeh‐Miller, Robinson, Read, & Ross, ), and (d) collaborations with non‐genetics professionals to provide genetic services for routine indications (Cohen & McIlvried, ; O'Shea et al, ). Per the 2018 National Society of Genetic Counselors (NSGC) Professional Status Survey, 62% of GCs are utilizing multiple service delivery models (National Society of Genetic Counselors, ) and genetics clinics are implementing online tools that improve efficiency by allowing patients to share their own medical information prior to a clinical appointment (Pritzlaff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators identified 15 different tasks performed by GCAs, many falling in the category of PRA. Furthermore, GCs who worked with GCAs increased their patient volumes on average by 60% (Pirzadeh‐Miller et al, ). As such, employing GCAs may be one way to help GCs spend a larger proportion of their time in session with patients.…”
Section: Discussionmentioning
confidence: 99%
“…There has been one study investigating GCA job responsibilities and the impact of GCAs on GC efficiency (Pirzadeh-Miller, Robinson, Read, & Ross, 2016). The investigators identified 15 different tasks performed by GCAs, many falling in the category of PRA.…”
Section: Discussionmentioning
confidence: 99%